1991
DOI: 10.1093/jnci/83.15.1072
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk After Iodine-131 Therapy for Hyperthyroidism

Abstract: Cancer incidence was studied in 10,552 patients (mean age, 57 years) who received 131I therapy (mean dose, 506 MBq) for hyperthyroidism between 1950 and 1975. Follow-up on these patients was continued for an average of 15 years. Record linkage with the Swedish Cancer Register for the period 1958-1985 identified 1543 cancers occurring 1 year or more after 131I treatment, and the standardized incidence ratio (SIR) was 1.06 (95% confidence interval = 1.01-1.11). Significantly increased SIRs were observed for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
7
8

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(151 citation statements)
references
References 0 publications
11
125
7
8
Order By: Relevance
“…In our base-case analysis we assumed there was no risk of radiation-induced thyroid cancer. Three reports (60,64,65) have found an increased relative risk while others (43,61,63) have not. Furthermore, some of them (60,63) have noted a small increased risk of other cancers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our base-case analysis we assumed there was no risk of radiation-induced thyroid cancer. Three reports (60,64,65) have found an increased relative risk while others (43,61,63) have not. Furthermore, some of them (60,63) have noted a small increased risk of other cancers.…”
Section: Discussionmentioning
confidence: 96%
“…(11,33,34,(36)(37)(38) 0.185 0.064 -0.306 0.99 Recurrent hyperthyroidism (11,31,(33)(34)(35)(36)38) 0.014 0 -0.045 95 Radio-induced thyroid cancer (31,43,61,63) 0.000 (0-0.008) § 0.83 Surgery Dysphonia (12,15,32,50) 0.030 0.015 -0.040 0.98 Hypothyroidism (11-15, 32, 39) 0.040 0.020 -0.054 0.99 * Quality-adjustment factors reflect the relative desirability of each health state or event. They usually result from expert judgment, values from the literature or values from measurements on a sample of subjects (40).…”
Section: Resource Usementioning
confidence: 99%
“…An unbiased discussion would have included two plausible explanations: the flawed data and the radiation hormesis. The authors also neglected to mention that in other studies of patients with hyperthyroidism and WDTC, RAIT has shown a protective effect on the risks of developing certain malignancies (4,5).…”
mentioning
confidence: 94%
“…En fait, la majorité des sujets suédois étaient adultes lors de l'exposition à l'iode 131, âge auquel la thyroïde est peu ou pas sensible à l'effet cancérigène des radiations ionisantes, comme l'ont montré les études après irradiation par voie externe. Ces observations ne permettent donc pas d'exclure l'effet cancérigène de l'iode 131 sur la thyroïde de l'enfant et de l'adolescent [7][8][9][10][11]. Cette mauvaise interprétation des données suédoises est une des raisons qui expliquent l'absence de mesures prophylactiques claires prises par les autorités soviétiques dans les premières semaines qui ont suivi l'accident.…”
Section: Incidence Des Cancers Thyroïdiens Dans Les Régions Limitrophunclassified